Ideological Issues of Protecting the Interests of the People of Uzbekistan in the Period of National Growth - Gulnora Khursandovna, Khudayberdieva; Manzura Abdumuradovna, Kholmirzaeva; Murat Mirzaevich, Allanazarov (International Journal of Psychosocial Rehabilitation, 2020)
The scientific article contains theoretical and practical views on the issue of ensuring the ideological and ideological security of the Uzbek people in the transition from national revival to the national upsurge. Concepts are given a philosophical definition, and their current development trends are shown.